Analisis Studi Kelayakan Bisnis pada Pengembangan UMKM Sembako di Desa Keramean dari Aspek Hukum, Aspek Pemasaran dan Aspek Keuangan - Hildah Meliyana; Abdur Rohman (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This study discusses the business feasibility analysis of MSMEs in basic food businesses in Keramean Village by considering legal, marketing, and financial aspects. Researchers use a quantitative approach with the least square method. Collection of data on the sale of basic food prices through interviews with business owners. This study aims to identify the potential success of basic food businesses and provide input for business owners in understanding the challenges and opportunities faced. The evaluation results show that April sales are more relevant than the previous month, this can happen because there is an increase in profit every month. This basic food business has great profit potential if managed properly, so it can be considered a promising business opportunity for MSMEs.